Pakistan’s Climate Conundrum: Revealing the Nexus Between Climate Change and Internal Migration - Nouman, Bibi Saira; Shams, Muhammad Nouman (Journal of Development and Social Sciences, 2024)
Migration due to climate change has become a common phenomenon worldwide, and Pakistan is not an exception. Climate-impacted migrants not only face socio-economic implications as security risks but migrant communities also suffer from exploitation. In Pakistan, Climate-induced migration poses challenges for every province. The study examines the relationship between international migration and climate change in Pakistan and evaluates the impact of climate change on different regions. Qualitative research with secondary data sources has been used. Using a thematic analysis, a researcher has examined the dataset from several aspects and highlighted different patterns and how they relate to one another. The study finds that internal migration is an adaptive strategy for flexibility to climate change and offers economic opportunities and challenges in migrated urban centers. The Research finds that migration can serve positively and effectively if adaptation strategies allow the vulnerable population to diversify their income resources along with the environmental changes. Therefore, study suggests that government should mitigate migration issues, reduce conflicts, and promote sustainable development.